2008
DOI: 10.1021/bi8013196
|View full text |Cite
|
Sign up to set email alerts
|

Correlating AMPA Receptor Activation and Cleft Closure across Subunits: Crystal Structures of the GluR4 Ligand-Binding Domain in Complex with Full and Partial Agonists

Abstract: AMPA receptors are glutamate-gated ion channels that are essential mediators of synaptic signals in the central nervous system. They form tetramers that are assembled as combinations of the subunits GluR1-4, each of which contains a ligand-binding domain (LBD). Crystal structures of the GluR2 LBD have revealed an agonist-binding cleft, which is located between two lobes and which acts like a Venus flytrap. In general, agonist efficacy is correlated with the extent of cleft closure. However, recent observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 55 publications
(107 reference statements)
2
34
0
Order By: Relevance
“…In addition, dynamics near the lobe interface suggest that large-scale lobe motions may be present when the LBD is bound to IW (21,23). In contrast, when the wild type LBD is bound to kainate, the lobes are in a relatively open orientation in all crystal structures to date (4,18,24,25), and this is supported by the average structure determined using NMR spectroscopy (15). The idea has been that the lobes remain separated by a steric clash between the isoprenyl group of kainate and the side chain of Leu-650 (3,18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, dynamics near the lobe interface suggest that large-scale lobe motions may be present when the LBD is bound to IW (21,23). In contrast, when the wild type LBD is bound to kainate, the lobes are in a relatively open orientation in all crystal structures to date (4,18,24,25), and this is supported by the average structure determined using NMR spectroscopy (15). The idea has been that the lobes remain separated by a steric clash between the isoprenyl group of kainate and the side chain of Leu-650 (3,18).…”
Section: Discussionmentioning
confidence: 99%
“…Although the lobes are slightly open relative to glutamate, two interlobe H-bonds (Gly-451-Gly-653 and Tyr-450-H 2 O-Ser-652) produced by a 180°rota-tion of the peptide bond are present in all three copies. These H-bonds are absent in most crystal structures of partial agonists and have been absent in all previously determined structures of kainate-bound AMPA receptors (3,18,24,25). Previous crystal structures have suggested that kainate prevents further lobe closure due to the steric clash between the side chain of Leu-650 with the isoprenyl group of kainate (foot-in-the-door mechanism) (18).…”
Section: Lobe-locking Mutations-the Ligand-binding Domain Ofmentioning
confidence: 98%
See 1 more Smart Citation
“…2; see also section V.A). Crystallography studies together with homology modeling of the AMPA receptor subunits GluA1 to GluA4 show that residues that directly interact with ␣-carboxyl and ␣-amino groups of glutamate, AMPA, and kainate are conserved (Armstrong et al, 1998;Armstrong and Gouaux, 2000;Bjerrum et al, 2003, Pentikä inen et al, 2003Gill et al, 2008) (Fig. 2).…”
Section: The Extracellular Ligand Binding Domainmentioning
confidence: 99%
“…The lobe opening of the GluA2 LBD bound to various antagonists or the apo state was measured relative to the A protomer of the structure of GluA2 LBD bound to glutamate (3DP6) as described by Gill et al (32). The distance between the ␤-carbons of P632 on each monomer within a dimer is given.…”
Section: Table 2 Lobe Orientation Of Glua2 Lbd Bound To Antagonistsmentioning
confidence: 99%